Research for performance and sensitivity of covered warrants hedging strategies with transaction cost and constant volatility in China market - SHI, YUE (2012)
With development of economy, covered warrant has been the most popular derivatives in China financial market. Choosing and appropriate hedging strategy is very important for the issuers of covered warrant avoid risk and get profit. The famous Black-Scholes model is the most widely used model for option pricing and hedging. However, because of the existence of transaction costs and it is unrealistic to hedge continuously in the real world, the Black-Scholes model and the delta dynamic hedging strategy which based on the Black-Scholes model are no longer effective. Thus this paper discussed and simulated 6 alternative discrete hedging strategies in evidence.